Using Translation Elongation Factor Gene to Specifically Detect and Diagnose Fusarium xylaroides, a Causative Agent of Coffee Wilt Disease in Ethiopia, East and Central Africa - Olal, S.; Olango, N.; Kiggundu, A.; Nanteza, A.; Matovu, E.; Wagoire, W.W. (J Plant Pathol Microbiol, 2018)
The present study presents the first report on the application of DNA-based polymerase chain reaction (PCR) for the specific detection and diagnosis of F usarium xylarioides (anamorph: G ibberrela xylarioides). Fusarium xylarioides is the causative agent of Coffee wilt disease (Tracheomycosis), and the disease is the most important economic constraint in Robusta coffee production in Uganda. The pathogen has two races, one pathogenic to Robusta coffee and the other to Arabica coffee, and not vice versa. Its laboratory diagnosis has been mainly based on microscopy, which is slow, has poor discriminative power, requires high expertise, only applicable on host plants with symptoms, and has since failed to detect the pathogen from the soil. Translation Elongation factor-1α (TEF-1α) gene from a F. xylarioides isolated from infected Robusta coffee plant was amplified by Fusarium genus specific primer then the PCR product sequenced. The sequence data was then used to design the specific primer. The primer-BLAST product was found to match only F. xylarioides sequences comprising 75% of the race pathogenic to Robusta and 25% to Arabica coffee. In vitro test by PCR showed the primer to be specific to only F. xylarioides amplifying a 284bp product and was able to differentiate F. xylarioides from all closely related species of Fusarium and other plant pathogens tested. More so it was able to amplify DNA from all the F. xylarioides isolates from different regions of Uganda, and amplified DNA concentrations as minute as 0.78 ng/µL.
Keywords: Translation elongation factor-1α; Coffee wilt disease; Giberella xylarioides